2023
DOI: 10.1002/pssa.202300236
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution of Molecular Orientation and Its Implication on Charge Transport in Floating Films of Conjugated Polymers

Abstract: Fabrication of uniform and oriented thin films of conjugated polymers (CPs) with controlled thickness is essential for the implementation of organic devices. Over the years, unidirectional floating film transfer method (UFTM) has emerged as a facile technique for the fabrication of oriented thin films but its distribution of orientation in vertical (thickness) direction has not been explored yet. To investigate this, thin films of nonregioregular poly(3‐hexylthiophene) are fabricated using UFTM with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…After the initial studies to investigate the effect of crystallinity and molecular orientation of CP thin films of RR-P3HTs fabricated using UFTM, dip-coating, and spin-coating; OFETs were fabricated in the BGTC device architecture as shown in Figure 1(B), for investigating anisotropic charge transport. In the previous reports by our group, it has already been reported that thin film fabrication by UFTM is oriented edge-on, which facilitates the facile in-plane charge transport [44,45]. In addition to this, Xue et al [46] reported that RR-P3HT dip-coated films are edge-on oriented.…”
Section: Electrical Characterizationmentioning
confidence: 75%
See 1 more Smart Citation
“…After the initial studies to investigate the effect of crystallinity and molecular orientation of CP thin films of RR-P3HTs fabricated using UFTM, dip-coating, and spin-coating; OFETs were fabricated in the BGTC device architecture as shown in Figure 1(B), for investigating anisotropic charge transport. In the previous reports by our group, it has already been reported that thin film fabrication by UFTM is oriented edge-on, which facilitates the facile in-plane charge transport [44,45]. In addition to this, Xue et al [46] reported that RR-P3HT dip-coated films are edge-on oriented.…”
Section: Electrical Characterizationmentioning
confidence: 75%
“…To circumvent these issues, thin film fabrication techniques such as dip coating [20] can be used, which can not only harness the enhanced molecular self-assembly of CPs but also solve the huge material wastage in the case of spin-coating. At the same time, the unidirectional floating-film transfer method (UFTM) [21], developed and improvised by our research group provides large area, uniform, anisotropic, and edge-on oriented thin film with the least material wastage. To access the quality of thin films fabricated by various methods in depth; optical, microstructural and electrical characterizations are very crucial.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent these issues, thin film fabrication techniques such as dip coating [ 21 ] can be used, which can not only harness the enhanced molecular self-assembly of CPs but also solve the huge material wastage in the case of spin coating. At the same time, the unidirectional floating-film transfer method (UFTM) [ 22 ] developed and improvised by our research group provides large area, uniform, anisotropic, and edge-on oriented thin films with the least material wastage. To access the quality of thin films fabricated by various methods in depth, optical, microstructural, and electrical characterizations are very crucial.…”
Section: Introductionmentioning
confidence: 99%